2018
DOI: 10.1177/1044389418781556
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempt Survivorship and Designation as a Concealable Stigmatized Identity

Abstract: Despite literature on unique challenges faced by people living with concealable stigmatized identities (CSIs), no research has explored this concept among suicide attempt survivors. Social network interviews with 26 attempt survivors about their family relationships were used to assess whether attempt-survivor status is consistent with CSI criteria. Participants concealed their attempt from 51% of family members and perceived that 46% of them held stigmatizing attitudes toward attempt survivors. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…It is estimated that 1.3 million adults make one or more suicide attempts each year in the United States (American Foundation for Suicide Prevention (AFSP), ), which puts them at a significantly elevated risk to die by suicide in the future (Harris & Barraclough, ). Because survivors of suicide attempts can be considered to have a concealable stigmatized status (Fulginiti & Frey, ), it is likely that disclosure of this stigmatized status to a trusted confidant will result in improved psychological well‐being (Chaudoir & Fisher, ). Prior research on disclosure of suicide attempts suggests the amount of information individuals disclose about their suicide attempt to trusted confidants (i.e., family members) is associated with better reactions to the disclosure, which is associated with decreased suicide risk factors (Frey & Fulginiti, ; Frey, Hans, & Cerel, ).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It is estimated that 1.3 million adults make one or more suicide attempts each year in the United States (American Foundation for Suicide Prevention (AFSP), ), which puts them at a significantly elevated risk to die by suicide in the future (Harris & Barraclough, ). Because survivors of suicide attempts can be considered to have a concealable stigmatized status (Fulginiti & Frey, ), it is likely that disclosure of this stigmatized status to a trusted confidant will result in improved psychological well‐being (Chaudoir & Fisher, ). Prior research on disclosure of suicide attempts suggests the amount of information individuals disclose about their suicide attempt to trusted confidants (i.e., family members) is associated with better reactions to the disclosure, which is associated with decreased suicide risk factors (Frey & Fulginiti, ; Frey, Hans, & Cerel, ).…”
mentioning
confidence: 99%
“…A concealable stigmatized identity is a socially devalued attribute that is not readily apparent to others, such as human immunodeficiency virus (HIV)‐positive status (Pachankis, ). Previous research has identified suicide attempt survivorship (henceforth, attempt survivorship) as a concealable stigmatized identity due to its possession of three core features that characterize concealable stigmatized identities: concealability, perceived stigmatization, and attribute salience to an individual’s identity (Fulginiti & Frey, ). Specifically, Fulginiti and Frey () demonstrate the concealability of attempt survivorship by reporting 29% of the familial relationships identified by suicide attempt survivors via a network analysis procedure involved no disclosure of attempt survivorship status.…”
mentioning
confidence: 99%
See 3 more Smart Citations